2003
DOI: 10.1063/1.1576971
|View full text |Cite
|
Sign up to set email alerts
|

Spatial resonator solitons

Abstract: Spatial solitons can exist in various kinds of nonlinear optical resonators with and without amplification. In the past years different types of these localized structures such as vortices, bright, dark solitons and phase solitons have been experimentally shown to exist. Many links appear to exist to fields different from optics, such as fluids, phase transitions or particle physics. These spatial resonator solitons are bistable and due to their mobility suggest schemes of information processing not possible w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Figure 76 shows snapshots of bright and dark (∼10 µm diameter) solitons, at the large (negative) resonator detuning. Their shape/size is independent of the shape/intensity of the driving beam [67]. This independence of boundary conditions (to their 'self-localization') characterizes solitons, as opposed to switched domains.…”
Section: Soliton Observationsmentioning
confidence: 97%
“…Figure 76 shows snapshots of bright and dark (∼10 µm diameter) solitons, at the large (negative) resonator detuning. Their shape/size is independent of the shape/intensity of the driving beam [67]. This independence of boundary conditions (to their 'self-localization') characterizes solitons, as opposed to switched domains.…”
Section: Soliton Observationsmentioning
confidence: 97%
“…The fundamental laser solitons have been observed experimentally in a dye laser with a saturable absorber [6,9,10] in a bistable semiconductor laser [11] and in a laserlike two-wave-mixing oscillator with a saturable absorber [12]. It was shown that they can be switched on and off by external addressing pulses in different transverse locations and they can move in the phase gradient (figure 3).…”
Section: Scalar Laser Solitons With Phase Topological Defectsmentioning
confidence: 99%
“…The regions themselves may be static or moving. Localized patterns have been discovered in many physical systems and their models. However, only a few examples are known in reaction−diffusion (RD) systems, namely, autonomous wave segments, breathing (oscillating) spots, localized oscillatory clusters, localized wave segments controlled by global negative feedback, oscillons (localized oscillatory spots), localized stationary spots, and localized waves . The main difference between autonomous wave segments and localized waves is that the former appear spontaneously and are observed as two or more wave segments moving in the same direction, whereas localized waves appear due to special initial conditions and can move in directions determined by the initial conditions (in particular, in opposite directions) …”
Section: Introductionmentioning
confidence: 99%